IMPLIKASI PENGOSONGAN KOLOM AGAMA DALAM KARTU TANDA PENDUDUK TERHADAP PEMENUHAN HAK KONSTITUSIONAL UMAT BAHA’I - Panjaitan, Anna Kostantia (Department of Constitutional and Administrative Law, Faculty of Law Universitas Negeri Semarang (UNNES)., 2018)
Religion?s column is important are mandatory in the civil certificate, eg Identity Card. Discharging the column of religion in the National Identity Card made Baha'i faiths feel equivalent to Atheism. The purpose of this study to examine why people do not want to Baha'i religion column in the Identity Card emptied and the implications of emptying the religion column on the fulfillment of the constitutional rights of Baha'i. This study uses sociological juridical, with qualitative research approach. Sources of data in this study were obtained from a source of primary data and secondary data sources. The primary data obtained through interviews and documentation. While the secondary data is legislation, books, law journals, and previous research. The results showed that (1) People do not want to Baha'i religion column in the National Identity Card emptied because this is a violation of their constitutional rights as citizens of Indonesia, which is the constitution of his rights protected by the state. (2) The implications of emptying the column of religion in the identity cards of the constitutional rights of Baha'i to fulfill the marriage certificate, certificate of birth for children Baha'i. Discharging the column of religion in the National Identity Card is a violation of constitutional rights. It is very significant impact on the fulfillment of the constitutional rights of Baha'i.